Konsekuensi terhadap Perekonomian Republik Indonesia Akibat Invasi Rusia ke Ukraina - Iswahyudi, Iswahyudi; Millatipuan, Meika Arifatull (Universitas Negeri Surabaya, 2024)
This study intends to examine the consequences of the conflict between Russia versus Ukraine in the Indonesian economy. The conceptual framework of this research refers to Peterson's theory with qualitative descriptive methods. There are five indicators in this study, namely supply chain, banking system, economic growth, stock markets, and rising inflation. The result is that the supply chain, economic growth, the Indonesian stock market and inflation are adversely affected by the conflict. Meanwhile, the banking system was not adversely affected, because the Indonesian side carefully did not make a decision to impose sanctions or prefer a neutral policy (non-block). This makes Russia not consider Indonesia as a target for the cyberbanking system, and maintain good cooperation in country business.